(:unas) unassigned - Chrysostomou, Christis (My University, 2019)
This is the mirror committee of the Technical Committee 250 (TC 250) of the European Standardization Body (CEN), it consists of 9 members from academia, governmental departments, as well as the industry, and oversees nine (9) subcommittees with a total of about 50 members. TC18 is responsible for the implementation of Structural Eurocodes in Cyprus and the chairman is participating in CEN/TC250 as the representative of Cyprus. The appointment is valid to date